Single nucleotide polymorphisms of interleukins associated with hepatitis C virus infection in Egypt - Hany Khalil; Mohamed Arfa; Samir El-Masrey; Sherif M EL-Sherbini; Amal A Abd-Elaziz (Journal of Infection in Developing Countries)
Introduction: Hepatitis C is a liver disease caused by the hepatitis C virus (HCV). It can cause both acute and chronic hepatitis infection. Based on secretion of required cytokines upon infection, HCV can improve its own RNA and successfully complete the replication cycle. Importantly, single nucleotide polymorphisms (SNPs) are the most common type of genetic variation and have been found to play a critical role in modulation of cellular cytokine production and interaction. Methodology: A total of 100 blood samples were obtained from HCV patients, and 120 samples were obtained from healthy individuals who served as controls. SNPs of interleukin-10/592 (IL-10/592) and IL-4/589 were investigated for possible connection with HCV infection. Relative expression of IL-4, IL-6, and IL-10 were detected using real-time polymerase chain reaction and enzyme-linked immunosorbent assay Results: The polymorphisms of IL-10 revealed a high rate of mutant genotype CC within the location IL-10/592 in HCV patients and controls, which resulted in low secretion of IL-10. Interestingly, the findings here demonstrate a positive association between HCV load of viremia and the mutant genotype IL-4-589/TT accompanied with low expression IL-4 in comparison with IL-6 expression. Conclusions: These data suggest that the expression of IL-4 is inversely proportional to HCV load of viremia, and this connection is due to the high level of mutant genotype IL-4-589/TT in infected patients located in gene promoter and inhibits gene expression.